The Role of Psycotropic Diazepam as Liver toxicity Causes Damage to Histological and Hepatic Function - Krisnasari, Alfian Silvia; Sugianto, Yohanes (Jurnal Biologi Tropis, 2025)
Abuse of drugs and chemical compounds is increasing nowadays, one of the sleeping pills that is classified as a drug and is circulating in the community is Diazepam. Research on psychotropics that focuses on histopathological effects is important, because of the lack of research and information.The aim of this study was to determine changes in the histological structure of the liver and measured SGPT and SGOT due to diazepam, hopefully can increase awareness for used. This study used 12 mice divided into 4 groups by Simple Random Sampling method. The groups were control (Polyethylen Glycol 1000 1%) and 3 diazepam treatments (P1, P2 and P3) the concentration was 62.25; 83; 124.5 mg/kg/BW. Treatment were given for 28 days. SGPT and SGOT measured by Spectrofotometry on days 0, 7, 14, 21 and 28. After 28 days the mice were euthanized. The paraffin technique, hematoxylin and eosin staining, and scoring were used to prepare the samples, and the one-way anova T-test was used to assess the results. The damage histological structure of the liver observed was vacuolization, pyknosis, sinusoidal dilatation, cloudy swelling, fat and accumulation of Kupffer cells.  Damage increases as the dose increases. SGPT and SGOT enzyme showed were not significantly different.